Hydroxyapatite-based materials of marine origin: a bioactivity and sintering study - Piccirillo, C.; Pullar, R. C.; Costa, E.; Santos-Silva, A.; Pintado, Manuela; Castro, Paula M. L. (Materials Science and Engineering: C, 2016)
Single phase hydroxyapatite (HAp) and biphasic material hydroxyapatite/beta-tricalcium phosphate (HAp/beta-TCP) were obtained from a marine source (Atlantic cod fish bones). Here we report a study on the biological properties of these materials, including cytotoxicity, bioactivity and haemocompatibility. Results showed that the materials are not cytotoxic, neither in their powder nor in pellet form; indeed growth of Saos-2 cells was comparable to that of commercial. The haemolysis rate was lower than 2%; hence the materials can be classified as non-haemolytic. Moreover, when immersed in Simulated Body Fluid (SBF), crystal formation was observed on the surface of both materials. The sintering behaviour of the samples was also studied; both powders showed very high sinterability (density higher than 95% of the theoretical value). Overall, these results confirm the suitability of these materials for biomedical applications. info:eu-repo/semantics/publishedVersion